Cellular proteostasis: a new twist in the action of thymosin α1. (31st May 2018) - Stincardini, Claudia; Renga, Giorgia; Villella, Valeria; Pariano, Marilena; Oikonomou, Vasilis; Borghi, Monica; Bellet, Marina M.; Sforna, Luigi; Costantini, Claudio; Goldstein, Allan L.; Garaci, Enrico; Romani, Luigina
ABSTRACT: Introduction : Thymosin alpha 1 (Tα1) is a naturally occurring polypeptide of 28 amino acids, whose mechanism of action is thought to be related to its ability to signal through innate immune receptors. Tα1 (ZADAXIN®) is used worldwide for treating viral infections, immunodeficiencies, and malignancies. Owing to its ability to activate the tolerogenic pathway of tryptophan catabolism – via the immunoregulatory enzyme indoleamine 2, 3-dioxygenase – Tα1 potentiates immune tolerance mechanisms, breaking the vicious circle that perpetuates chronic inflammation in response to a variety of infectious noxae . Areas covered : Tα1 has never been studied in Cystic fibrosis (CF) in which the hyperinflammatory state is associated with early and nonresolving activation of innate immunity, which impairs microbial clearance and promotes a self-sustaining condition of progressive lung damage. Optimal CF treatments should, indeed, not only rescue CF transmembrane conductance regulator protein localization and functionality but also alleviate the associated hyperinflammatory pathology. Because of the inherent complexity of the pathogenetic mechanisms, a multidrug approach is required. Expert opinion : By providing a multipronged attack against CF, i.e. restraining inflammation and correcting the basic defect, Tα1 favorably opposed CF symptomatology in preclinical relevant disease settings, thus suggesting its possible exploitation for 'real-life' clinical efficacy in CF. This could represent a major conceptual advance in the CF field, namely the proposal of a drug with the unique activity to correct CFTR defects through regulation of inflammation.